Frailty scoring in vascular and endovascular surgery: A systematic review. (June 2022) - Koh, Bernard JQW; Lee, Quinncy; Wee, Ian JY; Syn, Nicholas; Lee, Keng Siang; Jie Ng, Jun; Wong, Audrey LA; Soong, John TY; MTL Choong, Andrew
One in 10 independently living adults aged 65 years old and older is considered frail, and frailty is associated with poor postoperative outcomes. This systematic review aimed to examine the association between frailty assessments and postoperative outcomes in patients with vascular disease. Electronic databases – MEDLINE, Embase, and the Cochrane Library – were searched from inception until January 2022, resulting in 648 articles reviewed for potential inclusion and 16 studies selected. Demographic data, surgery type, frailty measure, and postoperative outcomes predicted by frailty were extracted from the selected studies. The risk of bias was assessed using the Newcastle–Ottawa Scale. The selected studies (mean age: 56.1–76.3 years) had low-to-moderate risk of bias and included 16 vascular (elective and nonelective) surgeries and eight frailty measures. Significant associations ( p < 0.05) were established between mortality (30-day, 90-day, 1-year, 5-year), 30-day morbidity, nonhome discharge, adverse events, failure to rescue, patient requiring care after discharge, and amputation following critical limb ischaemia. The strongest evidence was found between 30-day mortality and frailty. Composite 30-day morbidity and mortality, functional status at discharge, length of stay, spinal cord deficit, and access site complications were found to be nonsignificantly associated with frailty. With frailty being significantly associated with several adverse postoperative outcomes, preoperative frailty assessments can potentially be clinically useful in helping practitioners predict and guide the pre-, peri-, and postoperative management of frail with vascular disease.